Instilling the Concept of Scale and Comparison in Elementary School Matematics Lessons - Putri, Cony Fahriza Davina; Fiqri, Syafirah; Maulidha, Yuvitha Disha; Muhammad, Azamul Fadhly Noor (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2026)
Mathematics instruction at the elementary school level requires meaningful conceptual understanding so that students are not only able to memorize formulas but also apply mathematical concepts in their daily lives. One topic that demands deep conceptual comprehension is the concept of ratio. However, various studies indicate that elementary school students still experience difficulties in understanding the concepts of ratio and scale. This study aims to review research findings and relevant literature related to the embedding of ratio concepts in elementary mathematics learning. The method employed is a literature review, examining scientific journals, conference proceedings, and relevant books. The results of the review show that students’ difficulties are influenced by their cognitive developmental characteristics, as they are at the concrete operational stage, by instructional practices that remain abstract, and by the limited application of contextual learning approaches. Furthermore, the teacher’s role as a facilitator and provider of scaffolding, the use of appropriate instructional strategies, and the integration of ratio concepts with real-life contexts play an important role in enhancing students’ conceptual understanding. Meaningful mathematics learning is therefore key to embedding ratio concepts in a comprehensive and sustainable manner among elementary school students.